Indigenous Innovation for Health, Agriculture, and Environmental Sustainability in Africa - Isaac Msughter Peter; Velisiwe Gasa (Regional Journal of Information and Knowledge Management, 2026)
Rationale of Study – Far from being static relics of the past, Indigenous knowledge systems represent living, dynamic frameworks of innovation that increasingly command global academic and policy attention. This paper aimed to examine the intersection of Indigenous knowledge (IK) with contemporary challenges in three domains: health information systems, agriculture and food sovereignty, and environmental management. Methodology – The study employed a qualitative approach using a desk research design to source information from peer-reviewed literature, international policy frameworks, and documented case studies. The study obtained information from 345 documents from databases such as Web of Science, Scopus, Google Scholar, ScienceDirect, SpringerLink, Taylor & Francis Online, Wiley Online Library, SAGE Journals, and JSTOR and 128 articles were used for thematic analyses. Findings – Indigenous knowledge systems offer viable and innovative solutions to contemporary challenges in health information systems, agriculture, food sovereignty, environmental management, and climate adaptation. However, the continued marginalisation of Indigenous knowledge through colonial institutional structures limits its contribution to sustainable development. The study therefore concludes that strengthening Indigenous self-determination, protecting knowledge sovereignty, and promoting equitable knowledge co-production are essential to harnessing the full potential of Indigenous innovation in Africa and beyond. Implications – This study suggests that realising the full potential of Indigenous innovation requires radical, structurally inclusive partnerships that centre Indigenous self-determination, protect intellectual sovereignty, and enable genuine co-production of knowledge. Originality – This paper argues Indigenous knowledge systems are key to Western paradigms, emphasising their diversity in management and innovation. It explores Indigenous knowledge in the health, agriculture, and environmental sectors and presents a framework that illustrates Indigenous innovation across interconnected systems.